Leadership in Radiological Investigations: An Evaluation of Clinical Excellence and Regulatory Compliance at Eskag Sanjeevani Hospital, Kolkata, India - Poulami Gupta Banerjee (Public Health, 2026)
Background: The democratization of high-end radiological diagnostics remains a significant challenge in India's peripheral regions. The Eskag Sanjeevani Hospital, Kolkata, India, has addressed this gap in one of the States of India by implementing a robust Public-Private Partnership (PPP) model. Objective: This study evaluates the effectiveness of the radiological infrastructure of Eskag Sanjeevani Hospital, focusing on regulatory safety, operational efficiency, and financial accessibility. Also, this study aims to promote clinical awareness among physicians to increase CT scan prescription rates to a benchmark of 32% of OPD footfall—as demonstrated by the successful proactive imaging model in units A, B, C, and D of an Indian state—to facilitate early disease detection, timely treatment initiation, and improved recovery outcomes. Methods: A retrospective analysis of 5,215 diagnostic studies conducted across four district units (Unit A, Unit B, Unit C, and Unit D) in December 2025 was performed. Operational performance was measured against Turnaround Time (TAT) compliance. Results: The diagnostic network achieved a 99.9% completion rate (5,209 studies) with 99.5% compliance with stipulated TAT. The clinical workload was dominated by high-resolution respiratory and abdominal imaging, facilitated by advanced CT technology. Safety was validated by 100% adherence to the Atomic Energy Regulatory Board (AERB) certification. Conclusion: The State-specific leadership in radiology is characterized by a successful integration of high-speed technology and regulatory transparency, offering a scalable model for inclusive healthcare delivery in resource-constrained geographies